2020
DOI: 10.1002/1873-3468.13971
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for cystic fibrosis transmembrane conductance regulator inhibition: from molecular mechanisms to treatment for secretory diarrhoeas

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) is an unusual ABC transporter. It acts as an anion‐selective channel that drives osmotic fluid transport across many epithelia. In the gut, CFTR is crucial for maintaining fluid and acid‐base homeostasis, and its activity is tightly controlled by multiple neuro‐endocrine factors. However, microbial toxins can disrupt this intricate control mechanism and trigger protracted activation of CFTR. This results in the massive faecal water loss, metabolic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 178 publications
(270 reference statements)
0
5
0
Order By: Relevance
“…GO and KEGG analysis showed that AMK, PSW and SCF target genes were not only enriched in neurological pathways, including neuroactive ligand-receptor interaction and neurotransmitter receptor activities, but also contributed to digestive functions, such as protein digestion and absorption, as well as salivary secretion. Many of these effects were seemingly rather indirectly combating secretory diarrhea frequently occurring during IBD (Schiller, 1999), than directly interacting with the progression of IBD (Jonge et al, 2020). Additionally, given the high fiber in the components of HYJJ decoction and the improved gut health following ingestion of plant-based constituents (Carvalhana et al, 2012;Alferink et al, 2020), the intrinsic nature of these herb compounds was also beneficial for the gut recovery.…”
Section: Discussionmentioning
confidence: 99%
“…GO and KEGG analysis showed that AMK, PSW and SCF target genes were not only enriched in neurological pathways, including neuroactive ligand-receptor interaction and neurotransmitter receptor activities, but also contributed to digestive functions, such as protein digestion and absorption, as well as salivary secretion. Many of these effects were seemingly rather indirectly combating secretory diarrhea frequently occurring during IBD (Schiller, 1999), than directly interacting with the progression of IBD (Jonge et al, 2020). Additionally, given the high fiber in the components of HYJJ decoction and the improved gut health following ingestion of plant-based constituents (Carvalhana et al, 2012;Alferink et al, 2020), the intrinsic nature of these herb compounds was also beneficial for the gut recovery.…”
Section: Discussionmentioning
confidence: 99%
“…While the co-expression of aforementioned pan-neuronal markers establishes the neuronal nature of MENs, the expression of set of key genes in MENs suggests putative specialized functional roles of these subpopulations when they co-exist with NENs in adults. These include the expression of genes associated with putative sensory (Calcb) 115 , neuromodulatory (Ntf3) 116 , secretory (Cftr) 117 , immunomodulatory (Il18) 2 , hormone regulating (Ghrh) 118 , extracellular matrix (ECM)-modulating (Dcn), and motility-regulating roles (Slc17a9 or VNUT) 119 . These MEN-enriched or MEN-specific expression profiles suggest that MENs perform various roles in the regulation of diverse gastrointestinal functions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Division of Pediatrics, Department of Pediatric Gastroenterology, Wilhelmina Children's Hospital, University Medical Center Utrecht (UMCU), Utrecht University (UU), Utrecht, the Netherlands; 2 Regenerative Medicine Center, UMCU, UU, Utrecht, the Netherlands; 3 Department of Gastroenterology and Hepatology, Erasmus MC, University Medical Center, Rotterdam, the Netherlands; 4 Newborn Research Z ürich, Department of Neonatology, University Hospital Zurich and University of Zurich, Zurich, Switzerland; 5 Institute of Physiology, University of Zurich, Zurich, Switzerland; 6 Kinder-und Jugendmedizin, Helios Klinikum, Krefeld, Germany;…”
Section: Patients and Study Designmentioning
confidence: 99%
“…GCC ligand binding increases the intracellular cyclic guanosine monophosphate (cGMP) level, which triggers protein kinase–mediated activation of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel and inhibition of the sodium-proton exchanger NHE3. This dual action promotes the retention of salt and water in the gut lumen ( 2 , 5 ), and abnormally high GCC activity leads to diarrhea.…”
Section: Introductionmentioning
confidence: 99%